A Stochastic Capacity Expansion Model for an Electricity Generation Company (Dhaka University Journal of Science, 2025)
The business organizations in Bangladesh are operating their business by intuition based planning. They are not using scientific techniques for making decisions. But the scientific models can play an important role to maximize their profit and to save idle times, wastage of raw materials and finished products. As a result, the business organizations in our country fail achieve their goals.This is the case for electricity generation companies too. This research paper will focus on developing a stochastic capacity expansion model to help an electricity generation company. Capacity expansion problems are concerned with the timing of facility expansions and levels of investments to meet increasing demand. Since demand is difficult to forecast and expansion plans may need to change over time, stochastic programming offers a convenient way to solve these problems. In this research paper, we will develop a multi-stage stochastic programming model to formulate the real world problem which will satisfy the future demand of an electricity generation company. The model will help the company to find optimal investment in different power plants by allocating the limited resources and capacities to different power terminals.To observe whether the company can maximize the utilization of resources and minimize cost, and to demonstrate the applicability of our model, we will analyze a two-stage problem derived from this model. We will use mathematical programming language LINDO and LINGO for solving resulting SPs. We will also use MATHEMATICA to draw the continuous function.Dhaka Univ. J. Sci. 73(1): 19-30, 2025 (January)